Rapidly urbanizing food environments in Africa: Policies for achieving food and nutrition security - Mockshell, Jonathan (2023)
Food environments in Africa are changing rapidly due to urbanization spurred by economic growth, population increase, and rural-urban migration. This change poses a challenge to food and nutrition security in urban areas and African megacities such as Accra, Kinshasa, Lagos, and Nairobi, as consumers are increasingly demanding convenient processed food. With the wave of supermarket revolution, the urban food environments are responding by supplying affordable ultra-processed foods. The consequence is the triple burden of malnutrition with rising incidences of obesity, undernutrition and micronutrient deficiencies – leading to nutrition-related diseases.